Knowledge Management for Knowledge Society and Intergenerational Education - Jana Goriup; Vilma Alina Šoba (International School for Social and Business Studies, 2015)
The impact of globalization on contemporary post-modern society in the light of an aging population requires methods and techniques of education that are appropriate for young people and reflect (or accommodate) intergenerational learning. The purpose of this paper is to analyse, through empirical research and study of literature, the context of the elderly who are too often marginalized and to show the impact of the knowledge of society based on the use of modern information and communication technologies, on intergenerational learning. The authors analyse some of the consequences of the demographic changes and highlight the role and importance of intergenerational learning and collaboration for sustainability, especially in the Slovenian ageing society. We identify the role and importance of intergenerational learning for coexistence of generations. In the analysis of the empirical data of the conducted research, we conclude that the effectiveness of the knowledge society is influenced by both: the globalization processes and the intergenerational integration, as well as (and in particular) the cultural capital of younger generations and, last, but not least, the willingness of all generations to participate in the transmission and acquisition of knowledge.